Surgical Audit of Leakage after Open Surgical Repair of Perforated Peptic Ulcer - Ibrahim Asghar, Saira Fatima, Aisha Shaikh, Nargis Shaikh, Kanwal Qureshi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: to critically analyze the leakage after open surgical repair of peptic ulcer perforation. Methods: All patients who fulfilled the inclusion criteria and visited to surgical department SMBBMU, Larkana from September, 2018 to March, 2021 were included in the study. Informed consent was taken after explaining the procedure, risks and benefits of the study. X-ray abdomen erect posture, leukocyte count, and serum amylase were performed. After surgery, site of perforation and type of surgery were recorded. Patients were followed for 30 days in order to assess the leakage. Results: Mean ± SD of age was 42.6±8.5 years. Out of 203 patients included in the study, 145 (71.4%) were male while 58 (28.6%) were female, Leakage was noted in 13 (6.4%) patients. Conclusion: It is to be concluded that leakage was less likely prevalent after peptic ulcer perforation repair, but we cannot rule out residual confounders. Practical implication Keywords: Leakage, Peptic Ulcer Perforation, Repair, Peritonitis, Laparoscopy, Surgery.